2006
DOI: 10.1534/genetics.106.060418
|View full text |Cite
|
Sign up to set email alerts
|

A First-Generation Metric Linkage Disequilibrium Map of Bovine Chromosome 6

Abstract: We constructed a metric linkage disequilibrium (LD) map of bovine chromosome 6 (BTA6) on the basis of data from 220 SNPs genotyped on 433 Australian dairy bulls. This metric LD map has distances in LD units (LDUs) that are analogous to centimorgans in linkage maps. The LD map of BTA6 has a total length of 8.9 LDUs. Within the LD map, regions of high LD (represented as blocks) and regions of low LD (steps) are observed, when plotted against the integrated map in kilobases. At the most stringent block definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
41
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 33 publications
4
41
1
Order By: Relevance
“…Linkage disequilibrium (LD) has been defined as the non-random association between alleles at different loci (Phillips et al 2003;Khatkar et al 2006bKhatkar et al , 2008Odani et al 2006). Information concerning the structure of LD at the population level is crucial for interpretation and application of the results of genome wide association studies (Meuwissen and Goddard 2000;Khatkar et al 2006a;Bohmanova et al 2010;Lu et al 2012) and for determination of the statistical doi: 10.17221/56/2017-CJAS power of association studies (Khatkar et al 2007;Kim and Kirkpatrick 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Linkage disequilibrium (LD) has been defined as the non-random association between alleles at different loci (Phillips et al 2003;Khatkar et al 2006bKhatkar et al , 2008Odani et al 2006). Information concerning the structure of LD at the population level is crucial for interpretation and application of the results of genome wide association studies (Meuwissen and Goddard 2000;Khatkar et al 2006a;Bohmanova et al 2010;Lu et al 2012) and for determination of the statistical doi: 10.17221/56/2017-CJAS power of association studies (Khatkar et al 2007;Kim and Kirkpatrick 2009).…”
mentioning
confidence: 99%
“…Characterization of the empirical patterns of LD across the genome is important to improve our understanding the biological pathway of recombinations and selection results in the bovine genome (Khatkar et al 2006a;Bohmanova et al 2010). Furthermore, understanding the genomic landscape of bovine LD and variation in recombination rates facilitates the efficient design and analysis of association studies and greatly improves inferences from DNA marker polymorphism data based on population studies (Khatkar et al 2006b). The construction of a high-resolution LD map for the bovine genome will provide further insights into the effects of selection and evolutionary forces upon the genomes of breeds which have been selected for different agricultural purposes (McKay et al 2007).…”
mentioning
confidence: 99%
“…Additionally, until recently most studies have focused on bovine populations from developed 1 countries where they are subjected to intensive breeding, such as the Holstein breed, and these studies have suggested that significant LD among markers extends over several megabases (Farnir et al 2000;Tenesa et al 2003;Khatkar et al 2006;Thevenon et al 2007). As part of the whole bovine genome sequencing project, significant efforts are currently being carried out to identify a large number of SNPs by comparing hundreds of thousands of random sequences originating from a small set of individuals belonging to different populations with a reference sequence.…”
mentioning
confidence: 99%
“…A following step has been the construction of LD maps for the human (Maniatis 2002) and animal genomes (e.g., Khatkar et al 2006). LD maps are based on: (a) estimation of a linkage disequilibrium parameter, r, which has the same maximum absolute value as the statistics D9 of Lewontin (1964), and (b) use of a model of decay of disequilibrium leading to equations of Malecot's model for isolation by distance (Malecot 1964).…”
Section: Discussionmentioning
confidence: 99%
“…If the bias depends upon the distance between the adjacent SNPs as shown here then inferences on population structure and the evolution of the cattle population may not be fully correct. Khatkar et al (2006) carried out a LD map of bovine chromosome 6 using bulls from the Australian Holstein-Friesian. They estimated average coancestry by 0.012 using available pedigree information.…”
Section: Discussionmentioning
confidence: 99%